2018
DOI: 10.1182/bloodadvances.2018017095
|View full text |Cite
|
Sign up to set email alerts
|

Complement C5 but not C3 is expendable for tissue factor activation by cofactor-independent antiphospholipid antibodies

Abstract: The complement and coagulation cascades interact at multiple levels in thrombosis and inflammatory diseases. In venous thrombosis, complement factor 3 (C3) is crucial for platelet and tissue factor (TF) procoagulant activation dependent on protein disulfide isomerase (PDI). Furthermore, C5 selectively contributes to the exposure of leukocyte procoagulant phosphatidylserine (PS), which is a prerequisite for rapid activation of monocyte TF and fibrin formation in thrombosis. Here, we show that monoclonal cofacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 46 publications
5
36
0
2
Order By: Relevance
“…These aPLs, which are not reactive with the β2‐glycoprotein I cofactor, induce thrombosis independent of C5 and low‐density lipoprotein receptor‐related protein 8 (Lrp8) interacting with β2‐glycoprotein I. In contrast, C3 deficiency prevents amplified venous thrombus formation in an inferior vena cava thrombosis model in mice, consistent with the in vitro properties of aPLs in TF activation . Complement activation is also crucial in flow‐restricted venous thrombosis models in the mouse.…”
Section: Myeloid Cell Tf Activation In the Context Of Inflammationsupporting
confidence: 56%
See 1 more Smart Citation
“…These aPLs, which are not reactive with the β2‐glycoprotein I cofactor, induce thrombosis independent of C5 and low‐density lipoprotein receptor‐related protein 8 (Lrp8) interacting with β2‐glycoprotein I. In contrast, C3 deficiency prevents amplified venous thrombus formation in an inferior vena cava thrombosis model in mice, consistent with the in vitro properties of aPLs in TF activation . Complement activation is also crucial in flow‐restricted venous thrombosis models in the mouse.…”
Section: Myeloid Cell Tf Activation In the Context Of Inflammationsupporting
confidence: 56%
“…A distinction between these two types of EV is the affinity of TF for its ligand FVIIa. The PDI chaperone function enhances TF‐FVIIa affinity and is blocked by an antibody to TF, 10H10 , which reduces EV TF‐FVIIa affinity and markedly diminishes EV prothrombotic activity . Similarly, monocyte TF is activated by antiphospholipid antibodies (aPLs) that expose PS independent of PDI, but TF activation nevertheless requires the PDI oxidoreductase function and TF interactions that are blocked by anti‐TF 10H10 .…”
Section: Myeloid Cell Tf Activation In the Context Of Inflammationmentioning
confidence: 99%
“…Complement factors are crucial for venous thrombosis; C3 contributes to platelet and tissue factor procoagulant activation, and C5 is crucial for exposure of leukocyte procoagulant phosphatidylserine 89 . Muller-Calleja et al demonstrated that tissue factor activation is reduced by 16F16 (a PDI inhibitor) or 10H10 (an anti-tissue factor antibody that blocks PDI-tissue factor binding) and requires C3 but not C5 90 . Although this report is consistent with the hypothesis that PDI decrypts tissue factor by oxidizing the Cys186-Cys209 disulfide bond or through its chaperone activity, several studies undermined the hypothesis [91][92][93] .…”
Section: Thrombosismentioning
confidence: 99%
“…[43][44][45][46] From the perspective of pathophysiology HCQ, rapamycin and complement inhibitors are of particular interest, because these substances have been shown to inhibit signalling induced by aCL and anti-β2GPI, respectively. 33,45,47 Due to the high costs, specific complement inhibition by Eculizumab has been used only in few selected patients with variable results. 46 The lack of controlled studies also raises a concern of publication bias.…”
Section: Implications For Treatmentmentioning
confidence: 99%
“…Accordingly, C3deficient mice but not C5-deficient mice were protected from the prothrombotic effects of such aCL. 47 Therefore, an inhibitor of C5 like Eculizumab would be expected to be ineffective against TF activation by aCL, but might still be effective in preventing activation of the lytic complement complex.…”
Section: Implications For Treatmentmentioning
confidence: 99%